Lithologic characteristics and reservoir evolution of tight sandstones in the upper Triassic Xujiahe formation, northeast Sichuan Basin, China - Jianbo Gao; Ningliang Sun; Bing Hao; Jianhua Zhong; Zhiwei Chen; Zhifeng Cao (Unconventional Resources)
The Xujiahe Formation sandstones in the northeast Sichuan Basin are an important tight gas reservoir. Mineralogical, petrographic, and geochemical data were used to constrain the diagenesis and evolution of the reservoir quality. The Xujiahe sandstones are mainly classified as litharenite and feldspathic litharenite (lithofacies 1) and sublitharenite and quartz arenite (lithofacies 2). The clay mineral is dominated by illite and mixed-layer illite/smectite. The reservoir quality is poor, with a porosity of 0.1–5.6 % (average of 1.7 %) and permeability between 0.006–2.83 × 10−3 μm2 (average of 0.05 × 10−3 μm2). Sandstones develop a nanopore network with a strong heterogeneous pore structure and poor throat sorting. Intercrystalline micropores and microfractures are favorable pore types. The sandstones underwent significant diagenetic alterations and were dominated by mechanical compaction, volcanic ash alteration, authigenic clay minerals transformation, quartz and carbonate cementation, feldspar and rock fragment dissolution, and pressure dissolution. The diagenetic evolution enters the Telodiagenesis stage. The homogenization temperature (Th) of fluid inclusions within the calcite cement of lithofacies 1 is 102.7–198.2 °C, whereas it is 159.3–205.6 °C for lithofacies 2, indicating that lithofacies 1 experienced additional stages of carbonate cementation. The Th within quartz cement has high values. Lithofacies 1 is 102.4–209.7 °C, whereas lithofacies 2 is between 145.7 and 207.7 °C, indicating that pressure dissolution significantly decreased pore spaces in the late diagenetic stage. Depositional and diagenetic factors controlled reservoir quality. Good grain sorting and relatively big grain size are available for primary pore protection, whereas cementation evidently destroyed reservoir quality. Reservoir and porosity evolution processes indicate that lithofacies 2 has relatively good porosity. This study successfully improves the exploration and development efficiency of Xujiahe tight sandstone gas and can be applied to similar gas fields worldwide.